2015
DOI: 10.1007/s40257-015-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Resource Use and Costs in an Insured Population of Patients with Chronic Idiopathic/Spontaneous Urticaria

Abstract: BackgroundChronic idiopathic or spontaneous urticaria (CIU/CSU) impairs patients’ quality of life, and updated information on disease prevalence, treatment patterns, and disease burden is lacking.ObjectivesWe aimed to estimate these figures in a large US real-world claims database via a validated algorithm.MethodsIn this retrospective cross-sectional cohort study, we identified patients with CIU/CSU, estimated disease prevalence, comorbidities, and healthcare use (medications, office visits, emergency departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 29 publications
6
43
1
7
Order By: Relevance
“…This study indicates that approximately 25% of H1‐antihistamine‐refractory CSU patients have comorbid CIndU. Consistent with previous publications, other comorbidities in this patient population included asthma, allergic rhinitis, atopic dermatitis, allergies, and autoimmune diseases .…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that approximately 25% of H1‐antihistamine‐refractory CSU patients have comorbid CIndU. Consistent with previous publications, other comorbidities in this patient population included asthma, allergic rhinitis, atopic dermatitis, allergies, and autoimmune diseases .…”
Section: Discussionsupporting
confidence: 90%
“…For example, in the current analysis, 74% of patients with CU were women. This finding is consistent with retrospective database analyzes and other surveys where up to 70% of patients with CU and CIU were women (19,20). In addition, in the current analysis, 46% of patients with CU reported a history of nasal allergies, which was greater than the overall 28% of patients with psoriasis, and is comparable to the 43% of patients in the United States with CIU who reported a history of allergic rhinitis in a retrospective database analysis (19).…”
Section: Discussionsupporting
confidence: 90%
“…41 Interestingly, one study from Asia found no sex-specific difference and it was the study including only children (4-13 years). 32 Evaluating sex-specific differences in children < 15 years in three studies, 28,32,33 we found again no sexspecific difference. A sex-related prevalence shift from childhood to adulthood has been identified for allergies, like allergic rhinitis in adolescence 42,43 and asthma after the onset of puberty.…”
Section: Comparison With Other Studiesmentioning
confidence: 60%
“…Seven studies presented data stratified by sex. The point prevalence estimate for women was slightly higher than for men with overlapping corresponding 95% CIs based on random effect meta‐analysis: 1.3% (95% CI 0.1‐2.2) vs 0.8% (95% CI 0.2‐3.2) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation